Awareness Regarding Occupational Hazards Among the Dental Students of a Medical College of Nepal - Adhikari, S; Bhattarai, R (Journal of Nepalese Prosthodontic Society, 2022)
Introduction: Dental students, during their clinical and preclinical practices, are constantly exposed to a number of occupational hazards. Such exposures lead to various ailments and diseases. The study was done to assess the awareness regarding occupational hazards among dental students in College of Medical Sciences, Nepal. Methods: A questionnaire-based, descriptive cross-sectional study was conducted among the dental students from College of Medical Sciences, Nepal. Demographic details and awareness on different variables like bioaerosols, X-rays, blue light radiation, vibration, noise, posture, ergonomics, mercury vapour inhalation and percutaneous incidents, were assessed with the close-ended questions. Questionnaire was delivered to the participants in paper-printed forms. Data analysis was done using SPSS version 17. Chi-square tests were done to find the association between the variables to education and gender and the level of significance was set at p<0.05. Results: The mean knowledge score for the male students was higher than that for the female students and the difference was statistically significant (p<0.001). Fourth year students had the highest mean knowledge score (6.25±1.70) and second year students (2.71±2.43) had the lowest, and the scores were statistically significant (p<0.001). More than two-third of the students (72.8%) did not know that vibration causes peripheral neuropathy; more than three-fifth of them (61.7%) didn’t know that noise induced hearing loss is possible at dental settings and; about three-fifth of them (59.3%) did not know that X-ray hazards can be mitigated by barrier methods and position distance rule. Conclusion: The awareness regarding the radiation hazards, vibration hazards and noise induced hazards seem to be limited among the dental students. The study suggests introducing specific intervention programs like occupational safety seminars, trainings or workshops, for the dental students, before the commencement of their practical classes.